2012
DOI: 10.1155/2012/121797
|View full text |Cite
|
Sign up to set email alerts
|

Modern Aspects of Phototherapy for Atopic Dermatitis

Abstract: Phototherapy has still great importance in the treatment of atopic dermatitis, though costs, compliance, and long-term risks narrow its relevance. In spite of its long history, up to now, the therapeutic regimes are mostly empirical. Narrowband UVB und UVA1 are the most frequently applied regimens in atopic dermatitis with proven efficacy. However, even for these modalities randomized prospective and controlled studies are still pending. Advances in photoimmunology and molecular biology had demonstrated that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 87 publications
(93 reference statements)
0
39
0
Order By: Relevance
“…Various phototherapy modalities such as narrow-band UVB, UVA1 or UVA/UVB therapy are common treatment regimens of atopic dermatitis [38,39,40,41]. As the DLQI or the EQ-5D-VAS have not been used for evaluating UV therapy in atopic dermatitis patients yet, comparison of the present results is difficult [42].…”
Section: Discussionmentioning
confidence: 99%
“…Various phototherapy modalities such as narrow-band UVB, UVA1 or UVA/UVB therapy are common treatment regimens of atopic dermatitis [38,39,40,41]. As the DLQI or the EQ-5D-VAS have not been used for evaluating UV therapy in atopic dermatitis patients yet, comparison of the present results is difficult [42].…”
Section: Discussionmentioning
confidence: 99%
“…Narrowband UV-B and UV-A1 are the most frequently used efficacious regimens in patients with AD. 51 While the mechanism of action in AD has not been elucidated, it is thought to have local anti-inflammatory and immunosuppressive effects. A meta-analysis by Meduri et al 52 concluded that UV phototherapy is probably the most effective treatment modality in AD, with significant clinical improvement evident as early as 2 weeks.…”
Section: Phototherapymentioning
confidence: 99%
“…In adults, the long-term risk of skin melanoma appears to be greater with PUVA compared with UV-B. 51 Data on the risk of skin cancer in children receiving narrowband UV-B is lacking.…”
Section: Phototherapymentioning
confidence: 99%
“…The capacity of UVB-radiation to activate TLR3 responses in the skin could also potentially be harnessed for the treatment of certain dermatological conditions [49]. Patients with psoriasis respond well to narrow band UVB-radiation [101], and UVA/UVB-radiation was demonstrated to have beneficial effects in patients with atopic dermatitis [102]. However, given that such approaches can have potential long-term complications, for example skin cancer, alternative strategies to agonise TLR3 may be more applicable.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%